Corneal Mechanical Thresholds Negatively Associate With Dry Eye and Ocular Pain Symptoms - Spierer, Oriel; Felix, Elizabeth R.; McClellan, Allison L.; Parel, Jean Marie; Gonzalez, Alex; Feuer, William J.; Sarantopoulos, Constantine D.; Levitt, Roy C.; Ehrmann, Klaus; Galor, Anat (Investigative ophthalmology & visual science, 2016)
To examine associations between corneal mechanical thresholds and metrics of dry eye. This was a cross-sectional study of individuals seen in the Miami Veterans Affairs eye clinic. The evaluation consisted of questionnaires regarding dry eye symptoms and ocular pain, corneal mechanical detection and pain thresholds, and a comprehensive ocular surface examination. The main outcome measures were correlations between corneal thresholds and signs and symptoms of dry eye and ocular pain. A total of 129 subjects participated in the study (mean age 64 ± 10 years). Mechanical detection and pain thresholds on the cornea correlated with age (Spearman's ρ = 0.26, 0.23, respectively; both P < 0.05), implying decreased corneal sensitivity with age. Dry eye symptom severity scores and Neuropathic Pain Symptom Inventory (modified for the eye) scores negatively correlated with corneal detection and pain thresholds (range, r = -0.13 to -0.27, P < 0.05 for values between -0.18 and -0.27), suggesting increased corneal sensitivity in those with more severe ocular complaints. Ocular signs, on the other hand, correlated poorly and nonsignificantly with mechanical detection and pain thresholds on the cornea. A multivariable linear regression model found that both posttraumatic stress disorder (PTSD) score (β = 0.21, SE = 0.03) and corneal pain threshold (β = -0.03, SE = 0.01) were significantly associated with self-reported evoked eye pain (pain to wind, light, temperature) and explained approximately 32% of measurement variability (R = 0.57). Mechanical detection and pain thresholds measured on the cornea are correlated with dry eye symptoms and ocular pain. This suggests hypersensitivity within the corneal somatosensory pathways in patients with greater dry eye and ocular pain complaints.